Social well-being as an indicator of the level of adaptation of ethnic repatriates - Amitov, S. A.; Saribaeva, І. S.; Amantaeva, D. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2016)
In this article we can see problems of adaptation and integration of ethnic immigrants in modern Kazakh society. The object of study in this article is social feeling as an indica tor, that measure level and success of ethnic immigrants entering to the new socio-cultural area of Kazakh society, the subject of this article is adaptation of ethnic immigrants. The understanding of Social felling is like an important subjective human evaluation, which characterizes the degree of satisfaction of his needs and correspondence between social expectations and reality. The level of social feeling measured according to such parameters as evaluation of economic situation of family, evaluation of families’ financial conditions, relationships with local population. Here You can see a results of sociological research of ethnic immigrant’s social feeling, which acts as indicator of social adaptation’s success in modern Kazakh society. The authors provided social feeling as common characteristic, which is difficult to measure with sociological methods. The main difficulty is that this term has emotional, not rational character. By studying the problem and identifying the level of social well-being of ethnic immigrants, we are trying to determine their satisfaction of various sides of life. According our research, social well-being is considered as an integral component of ethnic immigrants` adaptation, as a result and index of the successful social adaptation process in the modern Kazakh society. The dynamics of social well-being is measured by indicators such as the assessment of the economic situation of the family (employment), the assessment of their own financial situation, the source of livelihood, relationships with the local population. We believe that ethnic immigrants` social well-being will be better with successful process of social adaptation to a new social environ ment. The analysis showed that the level of social well-being increasingly depends on its success, than active adaptation fact. The results show that adaptants` and disadaptans` good social well-beingcharacterized as goodsuccessful adaption. We can show a similar trend by unsuccessful adaptants, when a large share of these two respondent groups feel the new social reality rather bad. Thus,the approachallowedto consider thesubstantive side of theresearchaccording to specificconditions. The results of sociological research, referring to the established facts, allowto objectivelyexamine theproblemunder studyand present the conclusions.